Adubação verde em cultivo consorciado para produção de pimenta-biquinho (Capsicum chinense) em sistema orgânico - Dedini, Gabriel Ferraz de Arruda (2012)
The cultivation of peppers occurs in practically all regions of the country and is one of the crops that better integration exerts between the small farmer and the agribusiness. Thus it is desirable to develop technologies that combine the production of peppers with the conservation of natural resources, allowing recovery of soils and the economic stability of families that depend on this system. The aim of this study was to evaluate the effect of species and managements of green manure on mineral nutrition, growth and productivity of pepper-pout (Capsicum chinense). The experiment was conducted in the agricultural year 2010/2011 at the Center for Agricultural Sciences, UFSCar, Araras-SP. The treatments were a combination between green manure species: bean (Canavalia ensiformis DC) and sunn-hemp (Crotalaria juncea L.), and three forms of management of green manure in consortium with pepper-pout: green manures grown throughout the cycle of pepper, green manures managed (cut) in the flowering of pepper (75 days after transplanting, DAT), green manures handled at the first harvest of the fruits of pepper (90 DAT). And one more treatment (control), only with the pepper-pout plants, with mineral fertilization. The results showed that the species Crotalaria juncea and bean-pig conducted in consortia with plants of pepper-pout, when handled at 75 days after transplanting of vegetable crop, caused an increase in height and canopy diameter of pepper and fruit yield similar to the cultivation of pepper with exclusive use of mineral fertilizer. Overall, the releases of nutrients from biomass of green manure followed the nutritional demand of pepper plantspout, regardless of the time of cutting. But the bean-pig conducted throughout the cycle of pepper reduced fruit yield, probably by competition established between green manure and pepper.